2011
DOI: 10.4236/jbise.2011.48070
|View full text |Cite
|
Sign up to set email alerts
|

Discrete wavelet and modified PCA decompositions for postural stability analysis in biometric applications

Abstract: The aim of this study is to compare the Discrete wavelet decomposition and the modified Principal Analysis Component (PCA) decomposition to analyze the stabilogram for the purpose to provide a new insight about human postural stability. Discrete wavelet analysis is used to decompose the stabilogram into several timescale components (i.e. detail wavelet coefficients and approximation wavelet coefficients). Whereas, the modified PCA decomposition is applied to decompose the stabilogram into three components, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The DWT method for CoP signal decomposition has been applied in various fields. It has been used to analyze difference of postural stability based upon gender [ 45 ], determine effect of vestibular dysfunction on postural control [ 46 ], and evaluate difference of postural control ability after cochlear implant surgery [ 47 ]. In this study, we analyzed the difference of postural instability between AIS group ( n = 32) and control group ( n = 25) of the similar age, and interpreted differences in sensory information in terms of visual, vestibular, and somatosensory systems.…”
Section: Discussionmentioning
confidence: 99%
“…The DWT method for CoP signal decomposition has been applied in various fields. It has been used to analyze difference of postural stability based upon gender [ 45 ], determine effect of vestibular dysfunction on postural control [ 46 ], and evaluate difference of postural control ability after cochlear implant surgery [ 47 ]. In this study, we analyzed the difference of postural instability between AIS group ( n = 32) and control group ( n = 25) of the similar age, and interpreted differences in sensory information in terms of visual, vestibular, and somatosensory systems.…”
Section: Discussionmentioning
confidence: 99%
“…( 3 ) and ( 4 ). Similar to our approach, other researchers have used trunk tilt projection derived from an electromagnetic sensor, identified balance and stability behavior, and classified individuals on the basis of age, gender, height and weight [ 32 - 35 ]. Mean Velocity Displacement, Planar Deviation, and the ML and AP Trajectories [Eqns.…”
Section: Methodsmentioning
confidence: 99%
“…Amoud et al [ 8 ] showed the differences between age groups both using basic-EMD with separate analysis for x and y components and using complex-EMD where the interdependence between x and y components is not removed. Discrete wavelet decomposition and modified PCA to decompose the stabilogram into three components were proposed by Maatar et al [ 10 ]. He called these components: trend, rambling, and trembling.…”
Section: The Posturographic Signalmentioning
confidence: 99%